2012
DOI: 10.1128/aem.06751-11
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Strain wAlbB Enhances Infection by the Rodent Malaria Parasite Plasmodium berghei in Anopheles gambiae Mosquitoes

Abstract: Wolbachia, a common bacterial endosymbiont of insects, has been shown to protect its hosts against a wide range of pathogens. However, not all strains exert a protective effect on their host. Here we assess the effects of two divergent Wolbachia strains, wAlbB from Aedes albopictus and wMelPop from Drosophila melanogaster, on the vector competence of Anopheles gambiae challenged with Plasmodium berghei. We show that the wAlbB strain significantly increases P. berghei oocyst levels in the mosquito midgut while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 44 publications
(73 reference statements)
2
124
1
Order By: Relevance
“…Eliminating Asaia may facilitate the development of Wolbachia infections in these other vectors. The creation of Anopheles mosquito lines transinfected with a variety of Wolbachia strains will be worthwhile, given that some Anopheles-Wolbachia strain combinations may not be suitable for malaria control due to their propensity to increase certain Plasmodium parasites (36,56,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eliminating Asaia may facilitate the development of Wolbachia infections in these other vectors. The creation of Anopheles mosquito lines transinfected with a variety of Wolbachia strains will be worthwhile, given that some Anopheles-Wolbachia strain combinations may not be suitable for malaria control due to their propensity to increase certain Plasmodium parasites (36,56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality dynamics of mosquitoes pre-and postblood meal were conducted as previously described (35,36). wAlbB was injected into mosquitoes reared on conventional sugar, reared continuously on antibiotics, or reared continuously on antibiotics but supplemented with Asaia R as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though originally developed for IIT and life-shortening strategies, it was observed that infection with certain strains of Wolbachia dramatically reduced susceptibility to a range of pathogens, [99][100][101] though potentially increasing susceptibility to others. 102 Wolbachia are capable of spreading through insect populations as a heritable modification by manipulating the host's reproductive biology 84,103 -in other words, Wolbachia has the properties of a gene drive system. This raised the possibility that certain strains of Wolbachia might provide a complete gene-drive-plus-refractory-gene package.…”
Section: Gene Drive Systemsmentioning
confidence: 99%
“…Best known for its ability to invade invertebrate populations via modification of host reproductive systems (4), some Wolbachia-infected insects are protected from viruses and other pathogens (5)(6)(7)(8)(9)(10)(11)(12), while others have enhanced infection (13)(14)(15)(16)(17). Due to this ability to disrupt virus infection, there is an increased interest in employing Wolbachia as a means of biological control of arthropod-transmitted infectious diseases, such as dengue virus (18).…”
mentioning
confidence: 99%